Manipulation of kynurenine pathway for enhanced daptomycin production in Streptomyces roseosporus. (11th May 2013) - Liao, Guojian; Wang, Lei; Liu, Qing; Guan, Feifei; Huang, Yuqi; Hu, Changhu
<x xml:space="preserve">Abstract</x> Daptomycin is a cyclic lipopeptide natural product produced by Stretptomyces roseosporus, displaying good bactericidal activity against a wide range of gram‐positive pathogens. Daptomycin contains a 13 amino acid and kynurenine (Kyn) is essential for optimal activity of daptomycin. In this study, we characterized the Kyn pathway in S. roseosporus and investigated its role in supplying precursor for daptomycin biosynthesis. Two genes (dptJ and tdo) coding for tryptophan‐2, 3‐dioxgenase existed in the chromosome. dptJ is located in the daptomycin biosynthetic gene cluster, while tdo is in other locus. Disruption of dptJ or tdo resulted in reduced yield by ∼50%. The introduction of an additional copy of dptJ but not tdo led to enhanced production of daptomycin by 110%. Furthermore, disruption of kyn encoding kynureninase showed improved daptomycin productivity by 30%. Our results demonstrated that the enhancement of Kyn supply through metabolic engineering approach is an efficient way to increase daptomycin production. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:847–852, 2013